2019
DOI: 10.1371/journal.pone.0227366
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal monitoring of KRAS-mutated circulating tumor DNA enables the prediction of prognosis and therapeutic responses in patients with pancreatic cancer

Abstract: BackgroundLiquid biopsies enable the detection of circulating tumor DNA (ctDNA). However, the clinical significance of KRAS-mutated ctDNA for pancreatic cancer has been inconsistent with respect to its prognostic and predictive potential.Methods and findingsA total of 422 blood samples were collected from 78 patients undergoing treatments for localized and metastatic pancreatic ductal adenocarcinoma. KRAS mutation in tissues and KRAS ctDNA levels in plasma were determined by RASKET and droplet digital polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 44 publications
8
61
2
3
Order By: Relevance
“…In a subgroup of 39 patients, who did not undergo surgery, Fisher exact test indicated that detection of ctDNA during the longitudinal follow-up was associated with prognosis (p=0.005), meanwhile Ca19-9 levels were not (p=0.692). Moreover, changes in the concentration of ctDNA during the first 6 months of chemotherapy were able to predict response to treatment, while changes in Ca19-9 levels were not (23). The inverse correlation between the concentration of ctDNA and the survival of patients was also confirmed in other studies (24,25).…”
Section: Circulating Tumor Dna (Ctdna) In Pancreatic Ductal Adenocarcsupporting
confidence: 54%
“…In a subgroup of 39 patients, who did not undergo surgery, Fisher exact test indicated that detection of ctDNA during the longitudinal follow-up was associated with prognosis (p=0.005), meanwhile Ca19-9 levels were not (p=0.692). Moreover, changes in the concentration of ctDNA during the first 6 months of chemotherapy were able to predict response to treatment, while changes in Ca19-9 levels were not (23). The inverse correlation between the concentration of ctDNA and the survival of patients was also confirmed in other studies (24,25).…”
Section: Circulating Tumor Dna (Ctdna) In Pancreatic Ductal Adenocarcsupporting
confidence: 54%
“…We analyzed mutated KRAS in cell-free DNA with discriminatory ddPCR assays and integrated results with CA 19–9 levels for association with relapse and survival endpoints. Numerous studies have unveiled the potential of the analysis of cell-free mutated tumor DNA as novel diagnostic [ 27 ], predictive [ 31 33 ] and prognostic [ 31 , 32 , 34 37 ] biomarker for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Частота выявления цоДНК в крови пациентов по данным включенных исследований разнится от 17 до 63%, при этом чаще цоДНК определяется при распространенных стадиях заболевания [7,14,16,17]. Такие различия во многом связаны с методологией исследований.…”
Section: Discussionunclassified
“…Кроме того, в ряде работ показано, что определение циркулирующей опухолевой ДНК (цоДНК) при повторных заборах крови может дать возможность мониторировать изменения, происходящие в опухоли в процессе лечения, а также оценивать распространенность процесса. Применение таких чувствительных методов определения мутаций в ДНК, как цифровая капельная ПЦР и секвенирование нового поколения, позволило повысить частоту определения цоДНК [4][5][6][7].…”
Section: Introductionunclassified